Investigating Antibiotic Resistance Pattern and Prevalence of Class I, II, III Integron Genes in K. Pneumoniae Isolated from Clinical Samples in Sahrekord, Iran - Marzeyeh Soleymanian; Elahe Tajbakhsh; Zahra Bam zadeh (Journal of Advanced Biomedical Sciences, 2018)
Background & Objective: Acquiring integron is an important factor in multidrug resistance in the intestinal gram negative microorganisms. The most common integron cassette contains the genes associated with resistance to a wide range of antimicrobial agents. The aim of this study was to determine the prevalence of class 1, 2 and 3 integron genes in Klebsiella pneumoniae strains which was isolated from clinical samples in Shahrekord.